Menuju Desa Harmoni: Sinergi Pendidikan, Kesehatan, Ekonomi, dan Lingkungan - Rizky Fauzi Hamdani; Paulus Dara Bani; Moch. Rizky Maulana; Surya Ramadhan; Nurlatifa Haulaini; Erpin Ardiansyah; M Allam Farras; Siti Jamilah; Putri Meisya; Rahma Khairunnisa; Syarah Syarah; Elina Nurni Ayu; Risma Risma; Rinta Sari; Nur Komala Dewi; Nabila Nabila; Eneng Maryati; Ellyani Baho; Daniel Dimor; Novita Kareth (Universitas Methodist Indonesia, 2025)
The Community Service Program (KKN) in Desa Selaawi, Sukaraja District, Sukabumi Regency, implemented four main programs: character education for elementary school students, stunting awareness for pregnant women and mothers with toddlers, the development of Situ Batu Karut tourism, and assistance for MSMEs in online marketing. The activities aimed to improve human resource quality and the local economy. The results showed increased participant understanding of character education and stunting prevention, strengthened tourism identity through the creation of a name sign, and the utilization of digital media to expand MSME product marketing. This program had a positive impact while emphasizing that it requires ongoing support and training to ensure sustainable outcomes.